Preoperative corticosteroid injections are associated with worse long-term outcome of surgical carpal tunnel release. (February 2014) - Vahi, Paul-Sander; Kals, Mart; Kõiv, Leho; Braschinsky, Mark
<x xml:space="preserve">Abstract</x> Background and purpose Failed closed treatment of carpal tunnel syndrome (CTS) is often followed by surgery. We investigated whether preoperative steroid injections could have a negative effect on the long-term outcome of the operation. Patients and methods 174 hands (164 patients) were operated on by a single surgeon at Tartu University Hospital in 2005. The patients were interviewed by telephone 5–6 years after the operation. Self-reported data were gathered retrospectively concerning the number of steroid injections received before the surgery and the perceived regression of symptoms (on a 100-point numeric rating scale) at the time of interview. The patients were also asked about the presence of specific symptoms of CTS if regression of their symptoms had not been complete. Results 93 of the 174 hands had complete regression of symptoms. Each additional injection was associated with an increased risk of occurrence of pain (RR = 1.1, 95% CI: 1.02–1-2), paresthesiae (RR = 1.1, CI: 1.1–1.2), and nocturnal awakenings (RR = 1.2, CI: 1.1–1.3). There was a weak association between the number of injections and the score given to regression of symptoms. Interpretation This is the first study to indicate that patients who received a greater number of local steroid injections preoperatively were more likely to have postoperative complaints associated with CTS.